Energetic, GHG, and economic analyses of electrified steam methane reforming using conventional reformer tubes. (15th January 2023) - Mehanovic, Dino; Al-Haiek, Alexandre; Leclerc, Philippe; Rancourt, David; Fréchette, Luc; Picard, Mathieu
Abstract: A concept for electrified Steam Methane Reforming (eSMR) based on reformer tubes is proposed as a pathway for hydrogen decarbonization. The proposed concept applies radiant heating elements to a conventional gas-fired reformer. A thermochemical model and a techno-economic framework are developed to evaluate process performance at various conditions and the economic potential of the proposed concept. A baseline scenario with feedstock and electricity priced respectively at 4/MMBtu and 0.04/kWh, and assuming 2% of fugitive methane emissions and 50 gCO2 eq/kWh, results in an LCOH of 1.53/kgH2 and a decarbonization cost of 38/tonCO2 . The techno-economic results demonstrate that the proposed eSMR process leads to lower LCOH than mainstream alternatives over a wide range of energy prices. The study shows that reformer tube electrification is both economically viable and technically feasible, and therefore has the potential to decarbonize hydrogen production at a low cost. Graphical abstract: Highlights: A retrofitting concept is presented for the electrification of steam methane reforming. Electrified reforming is more energy efficient than gas-fired reforming. Peak efficiency is reached between ambient pressure and conventional reformer pressure. Electrified reformer tubes are cost-competitive with mainstream alternatives. Grid-connected electric steam methane reforming has a best-case LCOH of 1.53/kgH2 .